Extending Constraint Preconditioners for Saddle Point Problems - Dollar, H (Unspecified, 2005)
The problem of finding good preconditioners for the numerical solution of a certain important class of indefinite linear systems is considered. These systems are of a block 2 by 2 saddle point structure. In "Constraint preconditioning for indefinite linear systems" SIAM J. Matrix Anal. Appl., 21 (2000), Keller, Gould and Wathen introduced the idea of using constraint preconditioners that have a specific 2 by 2 block structure for the case of the (2,2) matrix block being zero. We shall extend this idea by allowing the (2,2) block to be non-zero. Results concerning the spectrum and form of the eigenvectors are presented, as are numerical results to validate our conclusions.